The longitudinal course of pediatric acute respiratory distress syndrome and its time to resolution: A prospective observational study - Wong, Judith Ju Ming; Tan, Herng Lee; Sultana, Rehena; Ma, Yi-Jyun; Aguilan, Apollo; Lee, Siew Wah; Kumar, Pavanish; Mok, Yee Hui; Lee, Jan Hau (Frontiers in Pediatrics, 2022)
Background: The longitudinal course of patients with pediatric acute respiratory distress syndrome (PARDS) is not well described. In this study, we describe the oxygenation index (OI) and oxygen saturation index (OSI) in mild, moderate and severe PARDS over 28 days and provide pilot data for the time to resolution of PARDS (Tres), as a short-term respiratory specific outcome, hypothesizing that it is associated with the severity of PARDS and clinical outcomes. Methods: This prospective observational study recruited consecutive patients with PARDS. OI and OSI were trended daily over 28 days. Tres (defined as OI <4 or OSI<5.3 on two consecutive days) were described based on PARDS severity and analyzed with Poisson and logistic regression to determine its association with conventional outcomes [mechanical ventilation (MV) duration, intensive care unit (ICU) and hospital length of stay, 28-day ventilator free days (VFD) and 28-day ICU free days (IFD)]. Results: There were 121 children included in this study, 33/121(27.3%), 44/121(36.4%) and 44/121(36.4%) in the mild, moderate and severe groups of PARDS, respectively. OI and OSI clearly differentiated mild, moderate and severe groups in the first 7days of PARDS; however, this differentiation was no longer present after 7days. Median Tres was 4 (interquartile range: 3, 6), 5 (4, 7) and 7.5 (7, 11.5) days; p<0.001 for the mild, moderate and severe groups of PARDS, respectively. Tres was associated with increased MV duration, ICU and hospital length of stay and decreased VFD and IFD. Conclusion: The oxygenation defect in PARDS took progressively longer to resolve across the mild, moderate and severe groups. Tres is a potential short-term respiratory specific outcome which may be useful in addition to conventional clinical outcomes, but needs further validation in external cohorts.